2015
DOI: 10.1007/s00408-015-9708-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers’ Views on Using Lung Age as an Aid to Smoking Cessation Counseling for Patients with Chronic Obstructive Pulmonary Disease

Abstract: Purpose Smoking cessation is the primary goal for managing patients with chronic obstructive pulmonary disease (COPD) who smoke. However, previous studies have demonstrated poor cessation rates. The “lung age” concept (an estimate of the age at which the FEV1 would be considered normal) was developed to present spirometry data in an understandable format and to serve as a tool to encourage smokers to quit. Primary care physicians’ (PCPs) views of using lung age to help COPD patients to quit smoking were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The U.S. smoking cessation guidelines indicate that the smoking cessation rate can be improved nearly three-fold by increasing the time devoted to guidance in one session, total guidance time, and number of types of specialists providing guidance. In addition, we provided smoking cessation guidance and an incentive to cease smoking using lung age, as calculated by pulmonary function tests ( 30 ). Morris et al ( 31 ) and the U.S. Public Health Service ( 14 ) reported that repeated education by many healthcare professionals and feedback using lung age are effective strategies for encouraging continued treatment by patients with COPD.…”
Section: Resultsmentioning
confidence: 99%
“…The U.S. smoking cessation guidelines indicate that the smoking cessation rate can be improved nearly three-fold by increasing the time devoted to guidance in one session, total guidance time, and number of types of specialists providing guidance. In addition, we provided smoking cessation guidance and an incentive to cease smoking using lung age, as calculated by pulmonary function tests ( 30 ). Morris et al ( 31 ) and the U.S. Public Health Service ( 14 ) reported that repeated education by many healthcare professionals and feedback using lung age are effective strategies for encouraging continued treatment by patients with COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, even though the FEV 1 of stage I COPD patients was numerically normal (FEV 1 %pred ≥80%), the Δ lung age values of 53% stage I COPD patients exceeded the ULN, indicating that lung age may be more helpful than FEV 1 %pred for patients to be aware of their lung function impairment. As lung age makes it easier for patients to understand their lung function level and is also well accepted by the majority of primary care physicians 17 , we believe that lung age may be a useful tool to be applied in the assessment and management of chronic respiratory diseases with lung function impairment, especially in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…12 Confronting smokers with their SLA has been used by general practitioners and primary care providers as a tool to encourage them to quit smoking. 13,14…”
Section: Indroductionmentioning
confidence: 99%